2009
DOI: 10.1007/s11604-009-0336-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac-sparing radiotherapy for the left breast cancer with deep breath-holding

Abstract: We concluded that radiotherapy on the DIBH facilitates a reduction of the irradiated heart volume compared to FB and IG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…The greatest distance of the heart and the inner thoracic wall was measured during deep inspiration breath hold (1.7 cm). Craniocaudally the heart moved around 2 cm during deep inspiration compared to end inspiration (1.5 cm) [20].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The greatest distance of the heart and the inner thoracic wall was measured during deep inspiration breath hold (1.7 cm). Craniocaudally the heart moved around 2 cm during deep inspiration compared to end inspiration (1.5 cm) [20].…”
Section: Discussionmentioning
confidence: 95%
“…They were mostly performed on 4D computed tomographies (4D-CTs) and can not be extrapolated to DIBH [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, this highlights the importance of minimising both the dose to these structures and the volume being irradiated as much as possible. There has been considerable interest in developing modern technology for radiotherapy planning to avoid excess cardiac irradiation, by modulation of the dose around organs at risk (OAR) using intensity modulated radiotherapy (IMRT) [18,19], IMRT with simultaneously integrated boost [20], placement of heart blocks [21] and deep inspiratory breathholding (DIBH) and gated techniques [22][23][24][25]. Beam angle modulation remains a very simple, and, up until now, rather neglected way of achieving this outcome.…”
mentioning
confidence: 99%
“…Yet, research has shown an increased risk of cardiovascular-related morbidity and mortality in women who have received radiation therapy for breast cancer on the left side (Darby et al, 2013). A new radiation therapy technology, breathing adapted radiation therapy (BART), which uses the movement of the chest when the woman breathes to its advantage , was introduced to reduce the risk of cardiac events (Nemoto et al, 2009). In Sweden, BART was first introduced in a regional hospital in the south of Sweden in 2007, and it is now available in almost the whole country (RCC, 2018).…”
Section: Treatment and Women's Experiences Of The Treatment Trajectorymentioning
confidence: 99%
“…When the woman takes deep breaths the chest rises further away from the heart. The radiation is given only when the woman is in the right respiratory phase, in other words, when the chest is as far from the heart as possible Nemoto et al, 2009). There is a need to know how an active participation in radiation therapy, through breathing, is experienced by the women, especially since it is evident that women diagnosed with breast cancer experience increased levels of anxiety in connection with their radiation therapy treatment Schnur et al, 2009).…”
Section: Treatment and Women's Experiences Of The Treatment Trajectorymentioning
confidence: 99%